2001
DOI: 10.1152/ajplung.2001.280.1.l107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of dexamethasone-mediated interleukin-8 gene suppression in cultured airway epithelial cells

Abstract: The effects of dexamethasone, a glucocorticoid analog, on interleukin 8 (IL-8) gene expression were studied in cultures of primary human tracheobronchial epithelial cells and an immortalized human bronchial epithelial cell line, HBE1 cells. Dexamethasone inhibited IL-8 mRNA and protein expression in a concentration- and time-dependent manner. The inhibition did not occur at the transcriptional level since both nuclear run-on activity and IL-8 promoter-reporter gene expression assay revealed no significant effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 37 publications
(39 reference statements)
0
28
1
Order By: Relevance
“…Consistent with this, the protein synthesis inhibitor cycloheximide (CHX) did not diminish the inhibitory effect of dex on expression of IL-6, intracellular adhesion molecule (ICAM)-1 or COX-2 mRNAs (De Bosscher et al, 1997;Wissink et al, 1998). In other studies, CHX blocked the GCmediated suppression of urokinase plasminogen activator, COX-2 and CXCL8 mRNA (Chang et al, 2001;Chaudhary and Avioli, 1996;Chivers et al, 2006;Henderson and Kefford, 1993;Newton et al, 1998;Tobler et al, 1992). This implies that GC-induced gene expression is involved, and that transrepression is insufficient for gene suppression in some circumstances.…”
Section: Inhibitory Effects Of Gc Do Not Require De Novo Gene Expressmentioning
confidence: 80%
See 2 more Smart Citations
“…Consistent with this, the protein synthesis inhibitor cycloheximide (CHX) did not diminish the inhibitory effect of dex on expression of IL-6, intracellular adhesion molecule (ICAM)-1 or COX-2 mRNAs (De Bosscher et al, 1997;Wissink et al, 1998). In other studies, CHX blocked the GCmediated suppression of urokinase plasminogen activator, COX-2 and CXCL8 mRNA (Chang et al, 2001;Chaudhary and Avioli, 1996;Chivers et al, 2006;Henderson and Kefford, 1993;Newton et al, 1998;Tobler et al, 1992). This implies that GC-induced gene expression is involved, and that transrepression is insufficient for gene suppression in some circumstances.…”
Section: Inhibitory Effects Of Gc Do Not Require De Novo Gene Expressmentioning
confidence: 80%
“…In other cases data on the relative contributions of transcriptional and post-transcriptional mechanisms are contradictory. Dex did not strongly inhibit CXCL8 transcription in nuclear run-on experiments, but potently destabilized CXCL8 mRNA in bone marrow stromal cells, lung fibroblasts, epithelial cells or cell lines (Chang et al, 2001;Chaudhary and Avioli, 1996;Chivers et al, 2006;Tobler et al, 1992). In contrast, other…”
Section: Gcs Inhibit Gene Expression At the Transcriptional Level Butmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous reports have indicated that cellular control of IL-8/CXCL8 production is largely regulated at the posttranscriptional level (35,53,54). Experimental evidence suggests that binding of certain proteins to AU-rich regions in the 3Ј-untranslated regions of chemokine mRNAs modulates the stability of these mRNAs (55).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8/CXCL8 production is controlled at the level of transcription and mRNA stability (34,35). Because eotaxin did not affect cytokine induction of adhesion molecules or other chemokines, we reasoned that the mechanism of eotaxin/CCL11 suppression of IL-8/CXCL8 release was likely to be posttranscriptional.…”
Section: Recombinant Eotaxin/ccl11 Reduces Steady State Levels Of Il-mentioning
confidence: 99%